The Relationship Between Arm Muscle Explosiveness And Hand-Eye Coordination With Top Service Accuracy in Volleyball Extracurricular Activities Female Student at SMA Negeri 1 Tembilahan Hulu - Ainul Mardiah; prima antoni; devit wilastra (Jurnal Olahraga Indragiri, 2023)
This type of research is correlational. This study aims to determine the relationship between Arm Muscle Explosiveness and Hand Eye Coordination with Upper Service Accuracy in Sawa Putri Volleyball Extracurricular Activities at SMA Negeri 1 Tembilahan Hulu. The population in this study amounted to 15 people. The sample in this study used total sampling, which consisted of 15 female students. The instruments used in this study were the Two-Hand Medicine Ball Putt test for the Arm Muscle Explosive Power, the Ballwerfen und-Fangen test for eye-hand coordination and the target field for the upper serve test. The results of this study concluded that there was a significant relationship between the explosive power of the arm muscles and the accuracy of serving in volleyball rcount = 0.72 > 0.514. And there is a significant relationship between hand eye coordination and accuracy of serving volleyball rcount = 0.86 > 0.514 and there is also a significant relationship between the explosive power of the arm muscles and hand eye coordination with accuracy of serving volleyball rcount = 0.86 > 0.514. Then the relationship between variable (X1) variable (X2) and variable (Y) can be calculated, the truth is tested by F-test and Fcount = 28.8 > 3.81 from the results of these calculations it can be concluded that there is a significant relationship between (X1X2Y) on Volleyball extracurricular activities for female students at SMA Negeri 1 Tembilahan Hulu.